Metabolism and spatial transcription resolved heterogeneity of glutamine metabolism in cervical carcinoma - Qian Liu; Jiayu Zhu; Guzalinuer Abulizi; Ayshamgul Hasim (BMC Cancer)
Abstract Background Reprogramming of cellular metabolism is a pivotal mechanism employed by tumor cells to facilitate cell growth, proliferation, and differentiation, thereby propelling the progression of cancer. A comprehensive analysis of the transcriptional and metabolic landscape of cervical squamous cell carcinoma (CSCC) at high resolution could greatly enhance the precision of management and therapeutic strategies for this malignancy. Methods The Air-flow-assisted Desorption Electrospray Ionization Mass Spectro-metric Imaging (AFADESI-MSI) and Spatial Transcriptomics techniques (ST) were employed to investigate the metabolic and transcription profiles of CSCC and normal tissues. For clinical validation, the expression of ASCT2(Ala, Ser, Cys transporter 2) was assessed using immune histochemistry in 122 cases of cervical cancer and 30 cases of cervicitis. Results The AFADESI-MSI findings have revealed metabolic differences among different CSCC patients. Among them, the metabolic pathways of glutamine show more significant differences. After in situ detection of metabolites, the intensity of glutamate is observed to be significantly higher in cancerous tissue compared to normal tissue, but the intensity is not uniform. To elucidate the potential factors underlying alterations in glutamine metabolism across tissues, we employ ST to quantify mRNA levels. This analysis unveils significant perturbations in glutamine metabolism accompanied by extensive heterogeneity within cervical cancer tissues. After conducting a comprehensive analysis, it has been revealed that the differential expression of ASCT2(encoded by SLC1A5) in distinct regions of cervical cancer tissues plays a pivotal role in inducing heterogeneity in glutamine metabolism. Furthermore, the higher the expression level of ASCT2, the higher the intensity of glutamate is in the region. Further verification, it is found that the expression of ASCT2 protein in CSCC tissues is significantly higher than that in normal tissues (105/122, 86.07%). Conclusions This finding suggests that the variation in glutamine metabolism is not uniform throughout the tumor. The differential expression of ASCT2 in different regions of cervical cancer tissues seems to play a key role in causing this heterogeneity. This research has opened up new avenues for exploring the glutamine metabolic characteristics of CSCC which is essential for developing more effective targeted therapies.